2014
DOI: 10.1309/lm604rqvkvlrfxor
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Platelet Clumps on Peripheral Blood Smears by CellaVision DM96 System and Microscopic Review

Abstract: The sensitivity of the DM96 for detecting PLT clumps can be maximized to 82.8% by reviewing the entire white blood cell screen and the entire PLT screen. Microscopic review of the blood smears yielded a PLT-clump detection rate of 99.0% when we examined the feather edge and the readable area of the smear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…Viewing of only a small segment of the PBS, either manually or by an automated morphological analyzer may cause misinterpretation of such cases leading to potentially inappropriate treatment decisions 4,5 . Previous automated digital microscopes fail to identify many of the specimens containing platelet clumps due to their narrow field of view, rendering manual microscope reviewing of samples with CBC‐derived thrombocytopenia essential 6,7,13‐15 . Previous digital microscopy users report limitations with respect to both platelets and RBC analysis, 14 and manual PBS analysis is recommended in various conditions 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Viewing of only a small segment of the PBS, either manually or by an automated morphological analyzer may cause misinterpretation of such cases leading to potentially inappropriate treatment decisions 4,5 . Previous automated digital microscopes fail to identify many of the specimens containing platelet clumps due to their narrow field of view, rendering manual microscope reviewing of samples with CBC‐derived thrombocytopenia essential 6,7,13‐15 . Previous digital microscopy users report limitations with respect to both platelets and RBC analysis, 14 and manual PBS analysis is recommended in various conditions 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Gulati et al collected 102 blood samples from 79 patients, whose ages ranged from 0 days (newborn) to 82 years. They reported a failure of the CellaVision to detect platelet clumps.…”
Section: Determination Of the Strengths And Weaknesses Of Available Pmentioning
confidence: 99%
“…Another relatively recently published study reported sensitivity in the range of 40.4% to 82.8% for the detection of platelet clumps/fibrin strands in blood smears by the CellaVision DM96 (Siemens Healthcare GmbH), which is an automated image analysis system. 6 These 2 systems may not be considered completely comparable because one (the CellaVision DM96) is semiautomated and uses stained blood smears for performing DIFFs and platelet scans, and the other (the Sysmex XE-5000) is fully automated and uses whole blood to perform the same analyses.…”
Section: Many Fibrin Strandsmentioning
confidence: 99%